Development of the Brief Educational Guide for Individuals in Need (BEGIN): A psychoeducation intervention for individuals at risk for psychosis. Issue 9 (22nd November 2021) - Herrera, Shaynna N.; Lyallpuri, Romi; Sarac, Cansu; Dobbs, Matthew F.; Nnaji, Obiora; Jespersen, Rachel; DeLuca, Joseph S.; Wyka, Katarzyna E.; Yang, Lawrence H.; Corcoran, Cheryl M.; Landa, Yulia
Abstract: Aim: Identification of individuals with psychosis risk (PR) through screening and specialized assessment is becoming more widespread in an effort to promote early intervention and improve recovery outcomes. PR individuals report interest in psychoeducation, though such interventions are currently lacking. Our goal was to develop a structured PR psychoeducation intervention grounded in theory and stakeholder feedback. Methods: By following a step‐by‐step intervention development model, we identified relevant conceptual frameworks, developed the content and format, and obtained stakeholder feedback. This process resulted in a 5‐session PR psychoeducation intervention, Brief Educational Guide for Individuals in Need (BEGIN), with content conveyed visually via a slideshow presentation. PR individuals ( n  = 5) and parents of PR individuals ( n  = 5) reviewed BEGIN's content and format, and provided feedback through semi‐structured qualitative interviews. Major themes were identified through iterative thematic analysis. Results: PR individuals and parents had a positive impression of BEGIN's materials and step‐by‐step format and psychoeducation about the PR condition. They indicated that the intervention was likely to encourage agency. PR participants emphasized the importance of a patient's decision regarding whether their family member(s) should participate in BEGIN. Parents reported that BEGIN is an important first step in treatment and offers a safe therapeutic environment. Feedback was then utilized to modify the intervention. Conclusions: BEGIN is desired by consumers and may lay the foundation for future engagement with treatment by facilitating agency. A feasibility trial is underway and future studies are needed to measure outcomes (e.g., treatment engagement) and evaluate BEGIN as an evidence‐based PR psychoeducation model.